1,1,1-Trifluoro-4-(thiophen-2-yl)-4-[(2-{[4,4,4-trifluoro-3-oxo-1-(thiophen-2-yl)but-1-en-1-yl]amino}ethyl)amino]but-3-en-2-one - Asiri, Abdullah M. (International Union of Crystallography, 2011)
The asymmetric unit of the diamine compound, C(18)H(14)F(3)N(2)O(2)S(2), consists of two molecules; the C=C double bond has a Z configuration in the C(4)H(3)S—C=C—C(=O)—C segment. The –NH—CH(2)—CH(2)—NH chain adopts a twisted U-shape. The amino group is an intramolecular hydrogen-bond donor to the carbonyl group; the intramolecular hydrogen bond generates a six-membered ring. In both molecules, the thienyl rings are disordered over two positions; the occupancies of the major components are 0.817 (4) and 0.778 (4) in one molecule and 0.960 (4) and 0.665 (4) in the other. One of the trifluoromethyl groups is disordered over two positions with the major component having 0.637 (8) occupancy.